2021
DOI: 10.1371/journal.pone.0246104
|View full text |Cite
|
Sign up to set email alerts
|

Predicting changes in cataract surgery health outcomes using a cataract surgery appropriateness and prioritization instrument

Abstract: Objective Determine whether items in a cataract surgery appropriateness and prioritization questionnaire can predict change in best corrected visual acuity (BCVA) and health related quality of life (HRQOL) following cataract surgery. Methods 313 patients with a cataract in Ontario, Canada were recruited to participate. BCVA was measured using the Snellen chart. HRQOL was measured using a generic instrument (EQ5D), a visual functioning instrument (Catquest-9SF), and an appropriateness and prioritization instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…[ 28 ] Lim et al . [ 41 ] also identified that Catquest-9SF scores were significantly improved when morbidity-related predictors such as safety, injury concerns, and ability to participate in daily activities were considered when prioritizing patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Lim et al . [ 41 ] also identified that Catquest-9SF scores were significantly improved when morbidity-related predictors such as safety, injury concerns, and ability to participate in daily activities were considered when prioritizing patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…При этом в соответствии с разработанным нормированием применительно к ФЭК-22 при «низком» КЖ ОПТ составлял 116-157 баллов; при «среднем» КЖ -158-191 балл и при «высоком» КЖ -192 и более баллов соответственно. Применительно к опроснику Catquest-9SF в соответствии с данными литературы [12] при ОПТ 9-18 баллов определяется «низкое» КЖ; 19-27 баллов -«среднее» КЖ и более 28 баллов -«высокое» КЖ соответственно.…”
Section: Ophthalmology In Russia 2023;20(3):497-501 актуальностьunclassified
“…1 Biomedical literature has described an increase in the number of cases of cataracts. This increase translates into a greater burden for health care systems, since untimely diagnosis and treatment can have immediate and long-term consequences such as the development of ocular complications, 6 causing increased dependence on others due to visual impairment, 5 increased risk of fractures, 7 decreased quality of life, 8 increased risk of mortality, 9,10 and economic losses for the individual, family and society. 11 Despite vision impairment and blindness being most common in people over the age of 50 12 and cataracts being a disease that can be treated by surgery.…”
Section: Introductionmentioning
confidence: 99%